2019
DOI: 10.1111/apa.14812
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical artery pH and base excess at birth are poor predictors of neurodevelopmental morbidity in early childhood

Abstract: Aim: We sought to evaluate the associations between umbilical artery pH and base excess and neurodevelopmental outcome at four years of age.Methods: This study comprised 84 588 singleton children born alive at term in 2005-2011 in the hospital district of Helsinki and Uusimaa in Finland. Data from the maternity hospital information system were linked to the data from the Medical Birth Register and the Hospital Discharge Register. Neurodevelopmental morbidity included cerebral palsy, epilepsy, intellectual or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…Umbilikal kordda hem pH hem de BE tüm GH'lerinda değerlendiren geniş serili retrospektif bir çalışmada, pH <7,00 ve BE <-16 olmasının mortalite ile ilişkili olduğu belirtilmiştir. Ancak bu eşik değerlerin serebral palsi ile ilişkisi gösterilememiştir (24). Zaigham ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Umbilikal kordda hem pH hem de BE tüm GH'lerinda değerlendiren geniş serili retrospektif bir çalışmada, pH <7,00 ve BE <-16 olmasının mortalite ile ilişkili olduğu belirtilmiştir. Ancak bu eşik değerlerin serebral palsi ile ilişkisi gösterilememiştir (24). Zaigham ve ark.…”
Section: Discussionunclassified
“…Sonuçlarımızda ise mortaliteyi değerlendirmek için en güçlü kan gazı parametresinin BE olduğu bulunmuştur. Hastaların klinik sonuçlarını öngörmede BE'nin tek başına kullanılması yerine, pH ile beraber kullanılması klinik anlamlılık değerini artırmaktadır (24). Ancak kan gazı parametreleri bir bütün olduğundan tüm parametreleri beraber değerlendirmek klinik sonuçlar hakkında fikir sahibi olmak için daha anlamlı olabilir (5).…”
Section: Discussionunclassified
“…The Doppler indices measured from the ductus venosus, umbilical arteries, cerebro-placental, and umbilico-cerebral Doppler ratios have been shown to correlate with the well-being of fetal growth restriction, which includes umbilical artery blood pH [7][8][9]. Umbilical artery pH (UA pH) is essential for assessing adverse pregnancy outcomes since it predicts the risk that neurodevelopmental problems will manifest in childhood [10]. There is a redistribution of fetal circulation in situations of FGR, so the Doppler ductus venous ow is changed, ranging from an increased pulsatility index to the absence or reversal of the A wave.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding long-term morbidity, Leinonen et al [15] carried out a population-based study and reported that APGAR scores < 4 are a better predictor of neurologic morbidity compared to those of the lower cutoff values of cord blood analysis. Kayani et al [16] compared children aged 2 years who had umbilical vein pH below 7.00 and normal APGAR, with that of controls with both normal pH and APGAR.…”
Section: Introductionmentioning
confidence: 99%